2016 International Congress of Entomology 2016
DOI: 10.1603/ice.2016.94147
|View full text |Cite
|
Sign up to set email alerts
|

Host and symbiont jointly control gut microbiota during complete metamorphosis

Abstract: Holometabolous insects undergo a radical anatomical re-organisation during metamorphosis. This poses a developmental challenge: the host must replace the larval gut but at the same time retain symbiotic gut microbes and avoid infection by opportunistic pathogens. By manipulating host immunity and bacterial competitive ability, we study how the host Galleria mellonella and the symbiotic bacterium Enterococcus mundtii interact to manage the composition of the microbiota during metamorphosis. Disenabling one or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 27 publications
(34 reference statements)
1
53
0
Order By: Relevance
“…However, the majority of the larval gut microbiota are purged during metamorphosis (Kingsley , Hammer et al. ; but see Johnston and Rolff ). It is more likely that these members of the gut flora are common in both butterflies and other insects because they are generally adapted to the insect gut environment (e.g., Chouaia et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the larval gut microbiota are purged during metamorphosis (Kingsley , Hammer et al. ; but see Johnston and Rolff ). It is more likely that these members of the gut flora are common in both butterflies and other insects because they are generally adapted to the insect gut environment (e.g., Chouaia et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the microbiome is of high importance in maintaining homeostasis of the host's body (Russell & Dunn, ; Chatelier et al., ). A recent study showed that host and symbiont communities cooperatively interact to maintain the midgut microbiota in a symbiotic balance (Johnston & Rolff, ), suggesting that the host needs more control over symbionts by means of AMP proteins. Symbionts may become pathogenic if they grow and reproduce uncontrollably, diverting resources away from growth and other needs of the host if not controlled by the host's immune system (Erdogan & Rao, ; Fujimori, ).…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus faecalis Andrewes and Horder) in the midgut of G. mellonella (Jarosz, ; Johnston & Rolff, ). This microbe is a heritable nutrient‐providing symbiont of G. mellonella (Bucher, ; Johnston & Rolff, ) that is transmitted vertically, from mother to offspring (Chen et al., ). It is probably among those rare microorganisms that can survive under the antibacterial properties of the G. mellonella diet.…”
Section: Discussionmentioning
confidence: 99%
“…Holometabolous insects, such as the Hymenoptera, shed the entire inner larval gut epithelium including their gut content during metamorphosis (Hakim, Baldwin, & Smagghe, ), which can lead to the clearance of symbionts from the gut. However, in some holometabolous insects, gut symbionts persist through metamorphosis due to actions of the host, the symbiont, or both (e.g., Johnston & Rolff, ). This might explain why in some attine ants late stage pupae do not differ from older workers in either absolute abundance of bacteria or in gut community diversity (Zhukova et al, ).…”
Section: Introductionmentioning
confidence: 99%